1994
DOI: 10.1115/1.2928855
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation of Frictionally-Excited Thermoelastic Instability in Automotive Disk Brakes Under a Drag Brake Application

Abstract: Thermoelastic instability in an automotive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 13 publications
2
36
0
Order By: Relevance
“…One purpose to incorporate chamfers and slots is to reduce squeal noise [14,15,16]. Relatively higher temperature at the pad surface than the interior will result in convex bending of the pad [17,18]. A slot will allow the material to bend and help avoid cracks.…”
Section: Brake Padmentioning
confidence: 99%
“…One purpose to incorporate chamfers and slots is to reduce squeal noise [14,15,16]. Relatively higher temperature at the pad surface than the interior will result in convex bending of the pad [17,18]. A slot will allow the material to bend and help avoid cracks.…”
Section: Brake Padmentioning
confidence: 99%
“…The system is symmetric about the mid-plane of the layer and all the modes are either symmetric or antisymmetric. We therefore modelled half of the system (half of the layer and one half-plane) and used antisymmetric boundary conditions at the symmetry plane, since Lee & Barber (1994) showed that the antisymmetric mode is always dominant for practical material combinations.…”
Section: Resultsmentioning
confidence: 99%
“…If more complete constitutive data are available, they are easily incorporated into the solution using equations (A 5) and (A 6) of Appendix A. The thermal expansion coe¯cient for many friction materials increases signi cantly with mean temperature, and this can cause systems to become unstable at later stages in a braking event (Lee & Barber 1994 The friction coe¯cient was taken as f = 0:4 and the layer semi-thickness as a = 10 mm. The half-planes were modelled as layers of nite thickness equal to 900 mm.…”
Section: Resultsmentioning
confidence: 99%
“…Again the assumption has to be made about the smearing of the pad, implying that circumferential variations of temperature and contact pressure cannot be predicted satisfactorily. It has been shown in previous work [22,23] that a pad also undergoes thermal deformation, called convex bending; furthermore temperature distribution is not constant along the circumference of a disc [24]. Thus, it is clear that these approaches are not sufficient to model the real behavior, instead a FEA model with complete three dimensional (3D) geometries of a disc and pads is required.…”
Section: Disc Brakes 3 31 Backgroundmentioning
confidence: 99%